Validity of the yo-yo intermittent recovery test level 1 for direct measurement or indirect estimation of maximal oxygen uptake in female soccer players - Martinez-Lagunas, V.; Hartmann, U. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To evaluate the validity of the Yo-Yo Intermittent Recovery Test Level 1 (YYIR1) for the direct assessment and the indirect estimation of maximal oxygen consumption (VO2max) in female soccer players compared with a maximal laboratory treadmill test (LTT). Methods: Eighteen female soccer players (21.5 ± 3.4 y, 165.6 ± 7.5 cm, 63.3 ± 7.4 kg; mean ± SD) completed an LTT and a YYIR1 in random order (1 wk apart). Their VO2max was directly measured via portable spirometry during both tests and indirectly estimated from a published non-gender-specific formula (YYIR1-F1). Results: The measured VO2max values in LTT and YYIR1 were 55.0 ± 5.3 and 49.9 ± 4.9 mL/kg·min, respectively, while the estimated VO2max values from YYIR1-F1 corresponded to 45.2 ± 3.4 mL/kg·min. Large positive correlations between the VO2max values from YYIR1 and LTT (r = .83, P < .001, 90% confidence interval = .64-.92) and YYIR1-F1 and LTT (r = .67, P = .002, .37-.84) were found. However, the YYIR1 significantly underestimated players` VO2max by 9.4% compared with LTT (P < .001) with Bland-Altman 95% limits of agreement ranging from -20.0% to 1.4%. A significant underestimation from the YYIR1-F1 (P < .001) was also identified (17.8% with Bland-Altman 95% limits of agreement ranging from -31.8% to -3.8%). Conclusions: The YYIR1 and YYIR1-F1 are not accurate methods for the direct assessment or indirect estimation of VO2max in female soccer players. The YYIR1-F1 lacks gender specificity, which might have been the reason for its larger error.